ASSESSING LABORATORY TECHNICIAN AND NURSE KNOWLEDGE, ATTITUDES, AND PRACTICES RELATED TO EFFECTIVE SPECIMEN COLLECTION AND HANDLING: AN OPPORTUNITY TO IMPROVE QUALITY IN SAUDI HEALTHCARE SETTINGS - Awad A. Alenazy1, Naif H. Al-Shammari2, Maryam M. Aldhafeeri3, Noura G. Alanzi4, Abdlmageed Ibrahim al-shdaid5, Raid Alitha Almutairi6 (Chelonian Research Foundation, 2022)
Clinical specimen quality is vital for accurate diagnostics, but errors in collection and handling threaten results. This cross-sectional survey of 322 laboratory technicians and nurses in Saudi hospitals assessed knowledge, attitudes, and reported practices related to specimen integrity. Results showed modest knowledge regarding rejection criteria, patient identification, test interfaces, and processing protocols among both groups. Technicians displayed better understanding of collection principles and tubes (mean scores 79% vs 68% for nurses, p<0.01). Nurses reported higher compliance with hand hygiene and documentation guidelines (88% vs 73%, p=0.032). Attitudes largely aligned with principles, but practice gaps emerged in labeling, order entry, and communication. Targeted quality improvement initiatives are warranted, including staff education, compliance monitoring, clarified role responsibilities, and standardized specimen management protocols. Closing knowledge and practice gaps can improve specimen quality to enhance diagnostic accuracy and patient care. Keywords: specimen collection, specimen handling, specimen rejection, clinical laboratory, nurse role, Saudi Arabia